2021
DOI: 10.3390/medicina57090930
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Decision-Making in Intensive Care Ten Years after a Law on Advance Directives in Germany

Abstract: Background and Objectives: Mortality on Intensive Care Units (ICUs) is high and death frequently occurs after decisions to limit life-sustaining therapies. An advance directive is a tool meant to preserve patient autonomy by guiding anticipated future treatment decisions once decision-making capacity is lost. Since September 2009, advance directives are legally binding for the caregiver team and the patients’ surrogate decision-maker in Germany. The change in frequencies of end-of-life decisions (EOLDs) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
4
0
2
Order By: Relevance
“…Data from web-based advance directive platforms indicated that during the COVID-19 pandemic, a significant increase in the demand for advance directive documentation was noted [ 19 ]. The completion rates of advance directives and legal documents among ICU patients reported in this study are similar to completion rates reported to corresponding patient collectives prior to the COVID-19 pandemic [ 6 ]. However, documentation of EOLD-relevant information about patient-sided advance care planning increased, especially in ICU patients admitted with COVID-19, compared to previous years and in comparison to data reported from other European centers [ 6 , 16 ].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Data from web-based advance directive platforms indicated that during the COVID-19 pandemic, a significant increase in the demand for advance directive documentation was noted [ 19 ]. The completion rates of advance directives and legal documents among ICU patients reported in this study are similar to completion rates reported to corresponding patient collectives prior to the COVID-19 pandemic [ 6 ]. However, documentation of EOLD-relevant information about patient-sided advance care planning increased, especially in ICU patients admitted with COVID-19, compared to previous years and in comparison to data reported from other European centers [ 6 , 16 ].…”
Section: Discussionsupporting
confidence: 80%
“…Although increasing over the recent decade, completion rates of advance directives remain low in Germany [ 6 ]. Seniors seem to complete an advance directive more frequently compared to people in the working age [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instrumente zur Vorausplanung für Situationen, in denen eine Person ihren Willen rechtlich nicht mehr erklären kann, existieren in Deutschland in Form der Patientenverfügung, Vorsorgevollmacht und Betreuungsverfügung. Der Bekanntheitsgrad dieser Vorsorgedokumente und deren Verbreitung in der Allgemeinbevölkerung nehmen seit Jahren stetig zu [1,2] und gewinnen im medizinisch-pflegerischen Berufsalltag immer mehr an Bedeutung [3,4,5]. Vorsorgedokumente bieten bei der Behandlung einwilligungsunfähiger Patienten eine Hilfe zur Ermittlung des Patientenwillens, ob durch Beschreibung der (nicht) gewünschten Behandlungsmaßnahmen in bestimmten Lebens-und Krankheitssituationen wie bei der Patientenverfügung oder Benennung eines Bevollmächtigten in der Vorsorgevollmacht bzw.…”
Section: Introductionunclassified